Upaya Meningkatkan Kemampuan Berhitung dan Minat Matematika Siswa dengan Metode Hitung Trachternberg - Heriyati Heriyati; Munasiah Munasiah (SAP (Susunan Artikel Pendidikan), 2022)
One of the mathematical abilities that students must have is the ability to count. The prerequisite in learning mathematics is learning to count, both of which are interconnected in supporting mathematical abilities. This study aims to improve students' numeracy skills and efforts to grow students' interest in mathematics. One of the solutions to the problem of mathematical arithmetic abilities is the Trachternberg method. If the rules of the Trachternberg mathematical method have been mastered then the calculations can be simple and fast in solving them. Classroom action research was used in this study, the approach was a quantitative and qualitative approach divided into 3 learning cycles. The research was conducted in November 2019 at SMPIT Ruhama Depok with a sample of 20 students. The results of the application of the Trachternberg method were an increase in students' numeracy skills and interest in mathematics; this was indicated by the percentage of interest of 80.09%, the percentage of completeness of numeracy skills of 75% with an average value of 77.